Single cell fabrication towards the realistic evaluation of a CNT-strung ZIF-derived electrocatalyst as a cathode material in alkaline fuel cells and metal-air batteries - Aiyappa, Harshitha Barike; Bhange, Siddheshwar N.; Sivasankaran, Vijitha P.; Kurungot, Sreekumar (ChemElectroChem, 2017)
The development of an electrocatalyst possessing all the vital requisites of an ideal electrode material, such as high porosity, high conductivity, and high intrinsic electrochemical activity, holds a decisive key in determining the activity of the triplephase boundary in many energy devices like fuel cells and metal-air battery systems. In the present work, highly porous cobalt-based ZIFs are strung along the highly conducive CNT backbone by using a simple one-pot technique at room temperature, which is then utilized to derive a porous, corrosion-resistant, Co nanoparticle-embedded electrocatalyst. Herein, for the first time, the single cell performance of the Co-ZIF-67-derived electrocatalyst has been evaluated by fabricating membrane electrode assemblies of alkaline exchange membrane fuel cell (AEMFC) and zinc-air battery (ZAB) systems. A maximum power density of 296 mW/cm(2) (vs. 317 mW/cm(2) for 40 wt.% Pt/C) and 60 mW/cm(2) (vs. 64 mW/cm(2) for 40 wt.% Pt/C) in the single cells of ZAB and AEMFC systems, respectively, establishes the practical proficiency of the homemade electrocatalyst for cathode applications during realistic system-level validations.
Keywords: Batteries; Carbon nanotubes; Composite materials; fuel cells; metal-organic frameworks